Helioseismic inference of the solar radiative opacity - Gaël Buldgen; Jean-Christophe Pain; Philippe Cossé; Christophe Blancard; Franck Gilleron; Anil K. Pradhan; Christopher J. Fontes; James Colgan; Arlette Noels; Jørgen Christensen-Dalsgaard; Morgan Deal; Sergey V. Ayukov; et al. (Nature Communications)
Abstract The Sun is the most studied of all stars, and thus constitutes a benchmark for stellar models. However, our vision of the Sun is still incomplete, as illustrated by the current debate on its chemical composition. The problem reaches far beyond chemical abundances and is intimately linked to microscopic and macroscopic physical ingredients of solar models such as radiative opacity, for which experimental results have been recently measured that still await theoretical explanations. We present opacity profiles derived from helioseismic inferences and compare them with detailed theoretical computations of individual element contributions using three different opacity computation codes, in a complementary way to experimental results. We find that our seismic opacity is about 10% higher than theoretical values used in current solar models around 2 million degrees, but lower by 35% than some recent available theoretical values. Using the Sun as a laboratory of fundamental physics, we show that quantitative comparisons between various opacity tables are required to understand the origin of the discrepancies between reported helioseismic, theoretical and experimental opacity values.